Reviewing an Argument for the Existence of the Necessary Being According to the Infinite Regression Presupposition - hamid alaeinejad (حکمت اسرا, 2015)
There are many arguments formulated for the existence of the necessary Being. In a general categorization, one can divide them to three groups: conditioned to the infinite regression, indifferent to the condition of infinite regression, conditioned to the invalidity of infinite regression. In this way, the majority of the arguments for the existence of God belong to the second and third groups. The subject of this study is an argument presented in an article in the 21th issue of this journal titled “Proof for the Necessary Being Using the Infinite Regression Principle: Looking at Avicenna's Argument and the Formation of a Novel Argument.” Presupposing the infinite regression and using some other philosophical principles, the authors of that article tried to present a novel argument categorized in the first group. In the present article, that argument is examined by a logical analysis. The findings of this article firstly show that the argument, regardless of the truth value of its premises, has some formal deficiencies, and secondly has a premise that generally is not true and needs revision. Formal deficiencies of the argument could be resolved by modifying some of the premises and fine-tuning the formal structure of the argument; but unless the false premise of the argument being replaced by another premise, or being modified in a way, the argument will remain incomplete.